Menentukan Kemungkinan Masuknya Calon Mahasiswa Baru pada Sebuah Perguruan Tinggi Swasta Manggunakan Teknik Klasifikasi Pohon Keputusan dengan Aplikasi RapidMiner 5.1 - Ananto, Petrus Dwi (Jurnal Informatika, 2015)
Classification techniques with the formation of the decision tree is a data processing technique enormous able to present the data into information that is easily understood by almost everyone didandingkan in table form. Usually, the results of data collection is in table form. But not everyone is able to read the tables quickly and accurately as you wish manufacturer, especially if the data is very large. Data in this study hundreds of data presented in tabular form. All prospective students information collected in one table with a lot of items, ranging from personal data, parents to home school. The resulting table will be difficult to understand so that the absorption of information becomes old and inaccurate. Presentation of information in the form of a decision tree into a proper alternative for the data very much. By using an application RapidMiner 5.1, the making of a decision tree data from prospective students to more easily and quickly so that the university management can see and know what are the factors that make potential students to continue the registration process to become a student.Â Keywords: data, information, decision tree, RapidMiner 5.0 application.